2008
DOI: 10.1590/s0102-311x2008001300002
|View full text |Cite
|
Sign up to set email alerts
|

Ensaio histórico-conceitual sobre a Atenção Primária à Saúde: desafios para a organização de serviços básicos e da Estratégia Saúde da Família em centros urbanos no Brasil

Abstract: This paper focuses on the experience with Primary Health Care as a strategy for reorganizing the health care model, based on reforms in this direction and their implementation in the Brazilian IntroduçãoApesar da enorme influência da medicina hospitalar, a figura do clínico geral ou do médico de família talvez simbolize ainda hoje uma imagem idealizada da medicina. Esse tipo de prática foi se configurando com formas e importância distintas em diversos países sendo atualmente denominada de atenção primária, o q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
166

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(199 citation statements)
references
References 14 publications
1
32
0
166
Order By: Relevance
“…The annual fluctuation of population coverage by the FHS in Guarulhos, with the prevalence of percentage decreases, shows the difficulty of expanding the strategy in large urban centers (22) . However, the care resources of PHC do not show lack of care for the population; nevertheless, as was also identified in the State of São Paulo (23) , poor coverage can be understood as the result of the way public health was developed, with a variety of traditional UBS based in large centers before the start of the FHS, which goes against small administrative divisions.…”
Section: Discussionmentioning
confidence: 99%
“…The annual fluctuation of population coverage by the FHS in Guarulhos, with the prevalence of percentage decreases, shows the difficulty of expanding the strategy in large urban centers (22) . However, the care resources of PHC do not show lack of care for the population; nevertheless, as was also identified in the State of São Paulo (23) , poor coverage can be understood as the result of the way public health was developed, with a variety of traditional UBS based in large centers before the start of the FHS, which goes against small administrative divisions.…”
Section: Discussionmentioning
confidence: 99%
“…This is worrying, especially in relation to the main point of access, where the majority of activities to avoid well-structured network, in which primary health care was provided by pediatricians, demonstrate the need for fresh adjustments to enable the new model to be understood and legitimized. 5,22 The main criticisms of the new model which emerged from the mothers' statements were the lack of doctors The infant death case study revealed the ESF's failure to monitor at risk children as one of the main determinants of infant death as well as indicating the link between other lapses in the health care provided, such as diffi culties in working in teams. The fact that responsibility for the death was avoided and blame placed on the mother refl ects serious problems in communication and professional conduct as well as probable corporate issues.…”
Section: Discussionmentioning
confidence: 99%
“…ibge.gov.br). para a superação de problemas estruturais e predomínio de estratégias de planejamento normativo, em consonância com o apontado por outros autores 2,6,14 .…”
Section: Metodologiaunclassified
“…A valorização do tema da atenção primária à saúde pode ser observada nos planos político e acadêmico, em âmbito nacional e internacional, nas propostas das agências internacionais e nos processos de reformas dos sistemas de saúde nos anos 1980 e 1990 2 .…”
Section: Introductionunclassified